Revitalization of Islamic Values-Based Curriculum: Integration of Religious Education in Mathematics Learning - Setiawan Setiawan; Warul Walidin; Zulfikar Ali Buto Siregar (Electronic Journal of Education, Social Economics and Technology, 2025)
This study discusses the urgency and strategy of integrating Islamic values in mathematics learning as part of the revitalization of the Islamic value-based curriculum. The main goal of this approach is to create an education that not only emphasizes the cognitive aspect, but also shapes the character and spirituality of students as a whole. Through the library research method, this study examines various scientific literature, books, and the latest research results related to the integration of Islamic values in mathematics education. The results of the study show that this integration can be carried out through thematic approaches, contextual, inquiry-based religious learning, and the use of technology such as interactive media and Islamic learning applications. The study also highlights the importance of the role of teachers, the need for contextual teaching tools, and the development of an integrative evaluation system that includes cognitive, affective, and spiritual aspects. Nevertheless, implementation in the field still faces challenges such as limited teacher training and lack of applicable assessment guidelines. The revitalization of the Islamic value-based curriculum is expected to be a strategic solution in forming a generation that is academically superior and has noble character.